Preparation method and application of carbon nanotube-supported PtIr diatomic Co alloy catalyst

By using carbon nanotube-loaded PtIr diatomic Co alloy catalyst at the anode of the proton exchange membrane fuel cell, the problems of high catalyst cost, easy toxicity and low stability are solved, and good hydroxide reaction activity and anti-CO toxicity performance are achieved. Reduced production costs.

CN119069731BActive Publication Date: 2025-01-17SHENZHEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411562448.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-17
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The proton exchange membrane fuel cell anode catalyst is costly, toxic and has low stability, especially in the presence of trace carbon monoxide.

Method used

The preparation method of carbon nanotube-supported PtIr diatom Co alloy catalyst is adopted, and the amount ratio of Pt and Ir is controlled by the folic acid template method, combining hydrothermal and high-temperature heat treatment, the electronic structure of diatomic active sites is regulated, and the catalyst resistance is enhanced. CO toxicity performance and stability.

Benefits of technology

It achieves low precious metal loading, good hydroxide reaction activity and high anti-CO toxicity performance, improves the long-term operation stability and electrochemical performance of the catalyst, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119069731B_ABST
    Figure CN119069731B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a carbon nanotube-supported PtIr diatomic Co alloy catalyst and its application. The present invention strictly controls the dosage ratio of Pt and Ir to adjust the diatomic form, and uses hydrothermal method and high-temperature heat treatment to uniformly anchor multiple components of the diatomic alloy on the carbon nanotube carrier, thereby obtaining diatomic active sites and using Co alloy to regulate the electronic structure of the diatomic sites. Compared with the vapor deposition method in the prior art, the folic acid template method of the present invention has the advantages of being simple and controllable, easy to scale up production, etc. At the same time, the folic acid compound used has the advantages of low cost and easy availability, and the amount of precious metals used in the obtained diatomic alloy catalyst is extremely low, which is conducive to the development of low-cost catalysts. The carbon nanotube-supported PtIr diatomic Co alloy catalyst synthesized by the present invention has good hydrogen oxidation reaction activity for the anode catalyst layer of a fuel cell, and its mass activity can reach 1.48 A mg Pt ‑1 @20 mV.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of proton exchange membrane fuel cells, and relates to a preparation method and application of a carbon nanotube-loaded PtIr diatomic Co alloy catalyst, in particular to an anode application in a fuel cell. Background Art

[0002] Proton exchange membrane fuel cells (PEMFC) have long been a focus of attention due to their advantages such as no pollution in products and high energy density. However, the current widespread application of proton exchange membrane fuel cells still requires the use of more precious metal catalysts at the anode and cathode to promote their reactions. This greatly increases the production cost. At the same time, the main means of industrial hydrogen production is methane reforming to produce hydrogen, and trace amounts of carbon monoxide (CO) will inevitably be introduced during the production process. Even trace amounts of CO will seriously poison the main active component of the anode catalyst - the precious metal platinum (Pt), resulting in a serious decline in device performance and reduced stability.

[0003] In recent years, single-atom catalysts have attracted widespread attention in the field of energy electrocatalysis due to their extremely high metal atom utilization rate and unique electronic structure. However, due to their high surface energy and single active center, single-atom catalysts are prone to aggregation during long-term operation, resulting in catalytic performance attenuation. In order to simultaneously achieve high atomic utilization and time durability of precious metal catalysts, the modification of single-atom sites by components such as nanoparticles / alloys can regulate the electronic structure of single atoms and reduce the aggregation and movement of single atoms during operation to stabilize the activity of the catalyst. At the same time, the electronic structure of the active site is regulated by auxiliary components, which is also beneficial to improving the catalyst's resistance to CO poisoning. It can be seen that the development of a hydrogen oxidation catalyst with synergistic effects of diatomic and alloy can effectively improve the activity of the hydrogen oxidation catalyst, and is conducive to improving the stability and anti-poisoning performance of the catalyst during long-term operation. This has certain reference significance for solving the current problems in the commercialization of proton exchange membrane fuel cells. Summary of the invention

[0004] The present invention aims to solve the problems of catalyst cost, easy poisoning and low stability during battery start-stop at the anode end of current proton exchange membrane fuel cells, thereby providing a method for preparing a carbon nanotube-loaded PtIr diatomic alloy catalyst with low noble metal loading, good hydrogen oxidation reaction activity and CO tolerance.

[0005] In order to solve the above technical problems, the present invention is implemented through the following technical solutions.

[0006] The present invention provides a method for preparing a carbon nanotube-supported PtIr diatomic Co alloy catalyst, comprising the following steps:

[0007] (1) placing folic acid in a solvent and stirring; then sequentially adding a cobalt source, a platinum source, an iridium source and a zinc source and continuing to stir; then adding hydrazine monohydrate and stirring thoroughly to obtain a metal-folic acid mixed solution;

[0008] (2) subjecting the metal-folic acid mixed solution to a hydrothermal reaction, and cooling it to room temperature to obtain a metal-folic acid nanotube precursor;

[0009] (3) washing the metal-folate nanotube precursor under high-speed centrifugation conditions;

[0010] (4) The washed product is freeze-dried and then calcined at high temperature under a protective gas atmosphere to obtain the product.

[0011] Preferably, the solvent in step (1) is selected from one or more of water and ethanol; more preferably, the solvent is selected from a water-ethanol mixed solvent; most preferably, the solvent is selected from a water-ethanol mixed solvent, and the volume ratio of water to ethanol is 5.5:8.

[0012] Preferably, the cobalt source in step (1) is selected from one or more of cobalt chloride, cobalt bromide, cobalt iodide, cobalt acetate, cobalt nitrate, cobalt carbonate and cobalt sulfate; more preferably, the cobalt source is selected from cobalt chloride.

[0013] Preferably, the platinum source in step (1) is selected from one or more of platinum nitrate, platinum dichloride, platinum tetrachloride, platinum sulfate, and platinum acetylacetonate; more preferably, the platinum source is selected from platinum acetylacetonate.

[0014] Preferably, the iridium source in step (1) is selected from one or more of iridium chloride, iridium nitrate and iridium acetate; more preferably, the iridium source is selected from iridium chloride.

[0015] Preferably, the zinc source in step (1) is selected from one or more of zinc chloride, zinc bromide, zinc nitrate, zinc sulfate and zinc acetate; more preferably, the zinc source is selected from zinc chloride.

[0016] Preferably, in step (1), the molar ratio of folic acid to the cobalt element in the cobalt source is 1.5-2.5:1; more preferably, the molar ratio of folic acid to the cobalt element in the cobalt source is 1.8-2.2:1.

[0017] Preferably, in step (1), the molar ratio of folic acid to the platinum element in the platinum source is 15-25:1; more preferably, the molar ratio of folic acid to the platinum element in the platinum source is 18-22:1.

[0018] Preferably, in step (1), the molar ratio of folic acid to the iridium element in the iridium source is 10-40:1; more preferably, the molar ratio of folic acid to the iridium element in the iridium source is 18-25:1.

[0019] Preferably, in step (1), the molar ratio of folic acid to zinc in the zinc source is 1-15:1; more preferably, the molar ratio of folic acid to zinc in the zinc source is 2-3:1.

[0020] Preferably, in step (1), the molar ratio of the platinum element in the platinum source to the iridium element in the iridium source is 0.7-1.5:1; more preferably, the molar ratio of the platinum element in the platinum source to the iridium element in the iridium source is 0.9-1.2:1.

[0021] Preferably, the molar volume ratio of folic acid to hydrazine monohydrate in step (1) is 1-4:20; more preferably, the molar volume ratio of folic acid to hydrazine monohydrate is 1:10.

[0022] It should be understood that, unless otherwise specified, the molar volume ratio in the context of the present invention should be understood in a conventional manner in the art, that is, the ratio of the amount of solid substance (in mmol) to the liquid volume (in mL). For example, when the molar volume ratio of folic acid to hydrazine hydrate is 1:8, if the amount of folic acid added is 0.5 mmol, the amount of hydrazine monohydrate added is 4 mL.

[0023] Preferably, the high temperature heating in step (2) is performed at a temperature of 100-200°C for a time of 60-180 min; more preferably, the high temperature heating is performed at a temperature of 120-160°C for a time of 90-150 min.

[0024] Preferably, the speed of the high-speed centrifugation in step (3) is 1000-15000 rpm, and the time is 1-10 min; more preferably, the speed of the high-speed centrifugation is 3000-8000 rpm, and the time is 3-7 min.

[0025] Preferably, the solvent used for washing in step (3) is selected from one or more of water and ethanol, and the number of washing times is 1-10 times; more preferably, the washing is specifically: washing with a water-ethanol mixed solvent for 1-10 times, and then washing with water for 1-3 times; most preferably, the washing is specifically: washing with a water-ethanol mixed solvent for 5 times, wherein the volume ratio of water to ethanol is 5.5:8, and then washing with water once.

[0026] Preferably, the freeze-drying temperature in step (4) is -30 to -60°C, and the time is 12 to 72 h; more preferably, the freeze-drying temperature is -40 to -50°C, and the time is 24 to 54 h.

[0027] Preferably, the protective gas in step (4) is selected from one or more of hydrogen, helium, argon, nitrogen, carbon dioxide, and a hydrogen-argon mixture.

[0028] Preferably, the high temperature calcination in step (4) is specifically: heating to 700-1200°C at a heating rate of 1-10°C / min and calcining for 30-180 min; more preferably, the high temperature calcination is specifically: heating to 800-1100°C at a heating rate of 3-6°C / min and calcining for 90-150 min.

[0029] The second aspect of the present invention provides a carbon nanotube-supported PtIr diatomic Co alloy catalyst prepared according to the above preparation method.

[0030] The third aspect of the present invention provides the use of the carbon nanotube-supported PtIr diatomic Co alloy catalyst prepared according to the above preparation method in the anode of a fuel cell.

[0031] Preferably, the application is specifically an anode hydrogen oxidation reaction and / or a cathode oxygen reduction reaction.

[0032] Compared with the prior art, the present invention has the following technical effects:

[0033] The present invention can control the diatomic form by strictly controlling the dosage ratio of Pt and Ir, and evenly anchor the diatomic alloy components on the carbon nanotube carrier by means of hydrothermal method and high temperature heat treatment, obtain the diatomic active site, and use Co alloy to control the electronic structure of the diatomic site. The synthesized catalyst has good hydrogen oxidation reaction activity, and its mass activity can reach 1.48 A mg Pt -1 @20 mV. The present invention can gasify the Zn species anchored in the carbon nanotubes during high-temperature calcination, thereby leaving more defects. This not only helps to prevent Pt, Ir, etc. from aggregating to form diatoms, but also increases the specific surface area of ​​the carbon nanotubes, allowing more active sites to participate in the reaction. The present invention adopts a folic acid template method to prepare a diatomic catalyst. Compared with the vapor deposition method in the prior art, the folic acid template method has the beneficial effects of simple synthesis and large-scale production. At the same time, the folic acid compound used has the advantages of low cost and easy availability, and the amount of precious metal used in the obtained catalyst is extremely low, which is conducive to the development of low-cost catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The PtIr prepared in Example 1 DA -Co NP Field emission scanning electron microscopy (FE-SEM) images of the catalyst.

[0035] Figure 2 This is the FE-SEM image of the folic acid metal complex prepared in Comparative Example 6.

[0036] Figure 3 The PtIr prepared in Example 1 DA -Co NP High-angle annular dark field-transmission electron microscopy (HAADF-TEM) image of the catalyst.

[0037] Figure 4 The PtIr prepared in Example 1 DA -Co NP X-ray diffraction (XRD) patterns of the catalysts.

[0038] Figure 5 The PtIr prepared in Example 1 DA -Co NP X-ray absorption near-edge spectra (XANEs) of the catalysts.

[0039] Figure 6 The PtIr prepared in Example 1 DA -Co NP Extended edge fine structure spectrum (EXAFS) of the catalyst's XANEs obtained by Fourier transform.

[0040] Figure 7 The PtIr prepared in Example 1 DA -Co NP The local electric field structure of the catalyst obtained by density functional theory (DFT) calculation.

[0041] Figure 8 The PtIr prepared in Example 1 DA -Co NP Comparison of hydrogen intermediate adsorption energies of catalysts calculated by DFT.

[0042] Fig. 9 The linear sweep voltammetry (LSV) graphs of the hydrogen oxidation reactions of the catalysts prepared in Example 1, Comparative Examples 1-3, and 20% commercial Pt / C catalysts.

[0043] Fig.10 PtIr with different Pt loadings prepared in Comparative Example 5 DA -Co NP LSV diagram of hydrogen oxidation reaction of the catalyst.

[0044] Fig.11 PtIr with different Co loadings prepared in Comparative Example 4 DA -Co NP LSV diagram of hydrogen oxidation reaction of the catalyst.

[0045] Fig.12 The PtIr prepared in Example 1 DA -Co NP Constant voltage test (IT) curve of the catalyst.

[0046] Fig.13 The PtIr prepared in Example 1 DA -Co NP Carbon monoxide stripping (CO stripping) curve of the catalyst. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail with reference to the following embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0048] Example 1

[0049] A carbon nanotube-supported PtIr diatomic Co alloy catalyst, the preparation method of which comprises the following steps:

[0050] (1) Place 110 mg (0.25 mmol) of folic acid in 13.5 mL of a water-ethanol mixed solution (volume ratio of water to ethanol: 5.5:8) and stir for 10 min. Then, add 29.74 mg (0.125 mmol) of cobalt chloride hexahydrate, 4.92 mg (0.0125 mmol) of platinum acetylacetonate, 3.73 mg (0.0125 mmol) of iridium chloride and 17 mg (0.125 mmol) of zinc chloride in sequence and continue stirring for 15 min. Then, add 2.5 mL of hydrazine monohydrate and stir for 15 min to obtain a metal-folic acid mixed solution.

[0051] (2) The metal-folic acid mixed solution was transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor, heated at 140 °C for 2 h, and then cooled to room temperature to obtain the metal-folic acid nanotube precursor.

[0052] (3) The metal-folate nanotube precursor was centrifuged and washed with a water-ethanol mixed solution (the volume ratio of water to ethanol was 5.5:8) at 6000 rpm for 5 min, and the washing number was 5 times; then, the precursor was centrifuged and washed with deionized water at 6000 rpm for 5 min.

[0053] (4) The washed product was freeze-dried with liquid nitrogen, transferred to a freeze dryer and freeze-dried for 2 days, and then heated to 900°C at a heating rate of 5°C / min under an argon atmosphere and calcined for 5 h to obtain a carbon nanotube-loaded PtIr diatomic Co alloy catalyst PtIr DA -Co NP.

[0054] Example 2

[0055] A carbon nanotube-supported PtIr diatomic Co alloy catalyst, the preparation method of which comprises the following steps:

[0056] (1) Place 96.8 mg (0.22 mmol) of folic acid in 13.5 mL of a water-ethanol mixed solution (volume ratio of water to ethanol: 5.5:8) and stir for 10 min. Then, add 23.792 mg (0.1 mmol) of cobalt chloride hexahydrate, 3.936 mg (0.012 mmol) of platinum acetylacetonate, 2.984 mg (0.01 mmol) of iridium chloride and 17 mg (0.125 mmol) of zinc chloride in sequence and continue stirring for 15 min. Then, add 2.5 mL of hydrazine monohydrate and stir for 15 min to obtain a metal-folic acid mixed solution.

[0057] (2) The metal-folic acid mixed solution was transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor, heated at 140 °C for 2 h, and then cooled to room temperature to obtain the metal-folic acid nanotube precursor.

[0058] (3) The metal-folate nanotube precursor was centrifuged and washed with a water-ethanol mixed solution (the volume ratio of water to ethanol was 5.5:8) at 6000 rpm for 5 min, and the washing number was 5 times; then, the precursor was centrifuged and washed with deionized water at 6000 rpm for 5 min.

[0059] (4) The washed product was freeze-dried with liquid nitrogen, transferred to a freeze dryer and freeze-dried for 2 days, and then heated to 900°C at a heating rate of 5°C / min under an argon atmosphere and calcined for 5 h to obtain a carbon nanotube-loaded PtIr diatomic Co alloy catalyst PtIr DA -Co NP .

[0060] Example 3

[0061] A carbon nanotube-supported PtIr diatomic Co alloy catalyst, the preparation method of which comprises the following steps:

[0062] (1) Place 79.2 mg (0.18 mmol) of folic acid in 13.5 mL of a water-ethanol mixed solution (volume ratio of water to ethanol: 5.5:8) and stir for 10 min. Then, add 23.792 mg (0.1 mmol) of cobalt chloride hexahydrate, 3.542 mg (0.009 mmol) of platinum acetylacetonate, 2.984 mg (0.01 mmol) of iridium chloride and 17 mg (0.125 mmol) of zinc chloride in sequence and continue stirring for 15 min. Then, add 2.5 mL of hydrazine monohydrate and stir for 15 min to obtain a metal-folic acid mixed solution.

[0063] (2) The metal-folic acid mixed solution was transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor, heated at 140 °C for 2 h, and then cooled to room temperature to obtain the metal-folic acid nanotube precursor.

[0064] (3) The metal-folate nanotube precursor was centrifuged and washed with a water-ethanol mixed solution (the volume ratio of water to ethanol was 5.5:8) at 6000 rpm for 5 min, and the washing number was 5 times; then, the precursor was centrifuged and washed with deionized water at 6000 rpm for 5 min.

[0065] (4) The washed product was freeze-dried with liquid nitrogen, transferred to a freeze dryer and freeze-dried for 2 days, and then heated to 900°C at a heating rate of 5°C / min under an argon atmosphere and calcined for 5 h to obtain a carbon nanotube-loaded PtIr diatomic Co alloy catalyst PtIr DA -Co NP .

[0066] Comparative Example 1

[0067] A carbon nanotube-supported Pt single-atom Co alloy catalyst, the preparation method of which comprises the following steps:

[0068] (1) Place 110 mg (0.25 mmol) of folic acid in 13.5 mL of a water-ethanol mixed solution (volume ratio of water to ethanol: 5.5:8) and stir for 10 min. Then, add 29.74 mg (0.125 mmol) of cobalt chloride hexahydrate, 4.92 mg (0.0125 mmol) of platinum acetylacetonate and 17 mg (0.125 mmol) of zinc chloride in sequence and continue stirring for 15 min. Then, add 2.5 mL of hydrazine monohydrate and stir for 15 min to obtain a metal-folic acid mixed solution.

[0069] (2) The metal-folic acid mixed solution was transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor, heated at 140 °C for 2 h, and then cooled to room temperature to obtain the metal-folic acid nanotube precursor.

[0070] (3) The metal-folate nanotube precursor was centrifuged and washed with a water-ethanol mixed solution (the volume ratio of water to ethanol was 5.5:8) at 6000 rpm for 5 min, and the washing number was 5 times; then, the precursor was centrifuged and washed with deionized water at 6000 rpm for 5 min.

[0071] (4) The washed product was freeze-dried with liquid nitrogen, transferred to a freeze dryer and freeze-dried for 2 days, and then heated to 900°C at a heating rate of 5°C / min under an argon atmosphere and calcined for 5 h to obtain a carbon nanotube-supported Pt single-atom Co alloy catalyst Pt SA -Co NP .

[0072] Comparative Example 2

[0073] A carbon nanotube-loaded Ir single-atom Co alloy catalyst. The preparation method thereof comprises the following steps:

[0074] (1) Place 110 mg (0.25 mmol) of folic acid in 13.5 mL of a water-ethanol mixed solution (volume ratio of water to ethanol: 5.5:8) and stir for 10 min. Then, add 29.74 mg (0.125 mmol) of cobalt chloride hexahydrate, 3.73 mg (0.0125 mmol) of iridium chloride and 17 mg (0.125 mmol) of zinc chloride in sequence and continue stirring for 15 min. Then, add 2.5 mL of hydrazine monohydrate and stir for 15 min to obtain a metal-folic acid mixed solution.

[0075] (2) The metal-folic acid mixed solution was transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor, heated at 140 °C for 2 h, and then cooled to room temperature to obtain the metal-folic acid nanotube precursor.

[0076] (3) The metal-folate nanotube precursor was centrifuged and washed with a water-ethanol mixed solution (the volume ratio of water to ethanol was 5.5:8) at 6000 rpm for 5 min, and the washing number was 5 times; then, the precursor was centrifuged and washed with deionized water at 6000 rpm for 5 min.

[0077] (4) The washed product was freeze-dried with liquid nitrogen, transferred to a freeze dryer and freeze-dried for 2 days, and then heated to 900 °C at a heating rate of 5 °C / min under an argon atmosphere and calcined for 5 h to obtain the carbon nanotube-loaded Ir single-atom Co alloy catalyst Irs A -Co NP .

[0078] Comparative Example 3

[0079] A carbon nanotube-supported Co particle catalyst, the preparation method of which comprises the following steps:

[0080] (1) Place 110 mg (0.25 mmol) of folic acid in 13.5 mL of a water-ethanol mixed solution (the volume ratio of water to ethanol is 5.5:8) and stir for 10 min. Then, add 29.74 mg (0.125 mmol) of cobalt chloride hexahydrate and 17 mg (0.125 mmol) of zinc chloride in sequence and continue stirring for 15 min. Then, add 2.5 mL of hydrazine monohydrate and stir for 15 min to obtain a metal-folic acid mixed solution.

[0081] (2) The metal-folic acid mixed solution was transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor, heated at 140 °C for 2 h, and then cooled to room temperature to obtain the metal-folic acid nanotube precursor.

[0082] (3) The metal-folate nanotube precursor was centrifuged and washed with a water-ethanol mixed solution (the volume ratio of water to ethanol was 5.5:8) at 6000 rpm for 5 min, and the washing number was 5 times; then, the precursor was centrifuged and washed with deionized water at 6000 rpm for 5 min.

[0083] (4) The washed product was freeze-dried with liquid nitrogen, transferred to a freeze dryer and freeze-dried for 2 days, and then heated to 900°C at a heating rate of 5°C / min under an argon atmosphere and calcined for 5 h to obtain carbon nanotube-supported Co particle catalyst Co NP .

[0084] Comparative Example 4

[0085] A carbon nanotube-loaded PtIr diatomic Co alloy catalyst with different Co loadings, the preparation method of which comprises the following steps:

[0086] (1) 110 mg (0.25 mmol) of folic acid was placed in 13.5 mL of a water-ethanol mixed solution (the volume ratio of water to ethanol was 5.5:8) and stirred for 10 min; then 44.61 mg (0.1875 mmol), 29.74 mg (0.125 mmol), 14.87 mg (0.0625 mmol), and 0 mg (0 mmol) of cobalt chloride hexahydrate were added respectively; then the types and amounts of platinum source, iridium source, and zinc source added in sequence were consistent with those in Experimental Example 1 and stirred for 15 min; then 2.5 mL of hydrazine monohydrate was added to each solution and stirred for 15 min to obtain metal-folic acid mixed solutions with different Co metal loadings.

[0087] (2) The metal-folic acid mixed solution with different Co metal loadings was transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor, heated at 140 °C for 2 h, and then cooled to room temperature to obtain the metal-folic acid nanotube precursor.

[0088] (3) The metal-folate nanotube precursors with different Co metal loadings were washed by centrifugation at 6000 rpm in a water-ethanol mixed solution (the volume ratio of water to ethanol was 5.5:8) for 5 min, and then washed five times by centrifugation at 6000 rpm in deionized water for 5 min.

[0089] (4) The washed product was freeze-dried with liquid nitrogen, transferred to a freeze dryer and freeze-dried for 2 days, and then heated to 900 °C at a heating rate of 5 °C / min under an argon atmosphere and calcined for 5 h to obtain carbon nanotube-loaded PtIr diatomic Co alloy catalysts with different Co metal loadings.

[0090] Comparative Example 5

[0091] A carbon nanotube-loaded PtIr diatomic Co alloy catalyst with different Pt metal loadings, the preparation method of which comprises the following steps:

[0092] (1) Place 110 mg (0.25 mmol) of folic acid in 13.5 mL of a water-ethanol mixed solution (volume ratio of water to ethanol: 5.5:8) and stir for 10 min. Then add 29.74 mg (0.125 mmol) of cobalt chloride hexahydrate, followed by 2.46 mg (0.00625 mmol), 4.92 mg (0.0125 mmol), 14.76 mg (0.0375 mmol), 24.6 mg (0.0625 mmol) of platinum acetylacetonate, 3.73 mg (0.0125 mmol) of iridium chloride and 17 mg (0.125 mmol) of zinc chloride, and continue stirring for 15 min. Then add 2.5 mL of hydrazine monohydrate and stir for 15 min to obtain a metal-folic acid mixed solution with different Pt metal loadings.

[0093] (2) The metal-folic acid mixed solution was transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor, heated at 140 °C for 2 h, and then cooled to room temperature to obtain the metal-folic acid nanotube precursor.

[0094] (3) The metal-folate nanotube precursor was centrifuged and washed with a water-ethanol mixed solution (the volume ratio of water to ethanol was 5.5:8) at 6000 rpm for 5 min, and the washing number was 5 times; then, the precursor was centrifuged and washed with deionized water at 6000 rpm for 5 min.

[0095] (4) The washed product was freeze-dried with liquid nitrogen, transferred to a freeze dryer and freeze-dried for 2 days, and then heated to 900 °C at a heating rate of 5 °C / min under an argon atmosphere and calcined for 5 h to obtain carbon nanotube-loaded PtIr diatomic Co alloy catalysts with different Pt metal loadings.

[0096] Comparative Example 6

[0097] A folic acid template method complexed Co, Ir, Pt metal catalyst, the preparation method of which comprises the following steps:

[0098] (1) Place 110 mg (0.25 mmol) of folic acid in 13.5 mL of a water-ethanol mixed solution (volume ratio of water to ethanol: 5.5:8) and stir for 10 min. Then, add 29.74 mg (0.125 mmol) of cobalt chloride hexahydrate, 4.92 mg (0.0125 mmol) of platinum acetylacetonate, 3.73 mg (0.0125 mmol) of iridium chloride and 17 mg (0.125 mmol) of zinc chloride in sequence and continue stirring for 15 min to obtain a metal-folic acid mixed solution.

[0099] (2) The metal-folic acid mixed solution was transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor, heated at 140 °C for 2 h, and cooled to room temperature to obtain the metal-folic acid precursor.

[0100] (3) The metal-folic acid precursor was centrifuged and washed with a water-ethanol mixed solution (the volume ratio of water to ethanol was 5.5:8) at 6000 rpm for 5 min, and the washing number was 5 times; then, the precursor was centrifuged and washed with deionized water at 6000 rpm for 5 min.

[0101] (4) The washed product was freeze-dried with liquid nitrogen, transferred to a freeze dryer and freeze-dried for 2 days, and then heated to 900°C at a heating rate of 5°C / min under an argon atmosphere and calcined for 5 h to obtain folic acid-complexed Co, Ir, and Pt metal compounds.

[0102] Verification Example 1

[0103] First, the carbon nanotube-supported PtIr diatomic Co alloy catalyst PtIr prepared in Example 1 was examined by field emission scanning electron microscopy (FE-SEM). DA -Co NP The morphology of the folic acid metal complex prepared in Example 6 was tested, and the results were as follows Figure 1-2 As shown in the figure, it can be clearly observed that PtIr DA -Co NP The morphology and structure of carbon nanotubes, with some particles embedded in the carbon nanotubes (see Figure 1 ). In contrast, the compound formed by the folic acid complex metal compound synthesized without adding hydrazine monohydrate in Comparative Example 6 is a sheet-like structure (see Figure 2 ). Subsequently, the PtIr in Example 1 was analyzed by high-angle annular dark field spherical aberration corrected transmission electron microscopy (HAADF-TEM). DA -Co NP The results of the analysis revealed that there were obvious Co metal particles in the tubes and obvious PtIr metal diatomic pairs on the surface of the nanotubes (see Figure 3 ). X-ray powder diffractometer (XRD) was used to further evaluate the PtIr DA -Co NP The specific types of particles in the material indicate that PtIr DA -Co NP There are obvious diffraction peaks of Co particle species in the material (see Figure 4 ), which shows Figure 3 The particles in the sample are mainly Co-related species, and Pt and Ir metals do not form obvious metal particles. Figure 5 PtIr DA -Co NP By comparing the intensity shift of the white line peak, it can be found that the addition of Ir element causes the white line peak of Pt to shift significantly to a higher energy level, indicating that the Pt atom loses electrons to form a high-valent oxidation state. Figure 6 The corresponding Fourier transform extended edge fine structure spectrum (FT-EXAFS) shows that no obvious Pt-Pt bond structure is observed, verifying that Pt exists in atomic form. Figure 7 Theoretical calculation results show that there is an obvious electron transfer phenomenon between Co alloy and Pt and Ir diatoms (the green and yellow areas in the figure represent the consumption and accumulation of electrons, respectively). By comparing the adsorption energies of different metal sites in the catalyst for hydrogen intermediates, the activity differences between metal sites can be evaluated. Figure 8 It can be clearly seen that the Pt atomic site modified by Ir element has the lowest hydrogen adsorption energy, which can enable the hydrogen intermediate to react and adsorb and desorb quickly on the surface of the Pt site. DA -Co NP The contents of Pt and Ir elements are 2.4 wt% and 2.2 wt% respectively, and the content of Co element is 24.9 wt%.

[0104] Subsequently, the catalysts prepared in Example 1, Comparative Examples 1-3, and 20% commercial Pt / C catalyst were taken respectively to test their electrochemical properties. Specifically, a three-electrode system was used, 0.5 M H2SO4 was used as the electrolyte, and the LSV test was performed on the Shanghai Chenhua CHI760e electrochemical workstation. 2 mg of catalyst sample was mixed with 20 uL Nafion and 380 uL water and isopropanol (volume ratio 1:1) to prepare catalyst ink. Then 20 uL was added dropwise to the glassy carbon electrode and naturally air-dried to make a working electrode. In the LSV test, -0.1~0.4 V (vs. RHE) was selected as the scanning range in a hydrogen-saturated electrolyte and scanned at a scanning rate of 10 mV / s.

[0105] Test results such as Fig. 9 The results show that the hydrogen oxidation (HOR) catalytic performance of the material was evaluated under 20 mV and 50 mV conditions, and it was found that the PtIr prepared in Example 1 DA -Co NP It has a higher current density than other samples. DA -Co NP It has a higher limiting current platform, and its unit mass activity can reach 1.48 A mg at 20 mV overpotential relative to the reversible hydrogen electrode (RHE). Pt -1 This suggests that PtIr DA -Co NP Possess good HOR catalytic performance.

[0106] In order to further compare the effect of metal ratio on the catalytic performance of the samples, control experiments of Comparative Examples 4 and 5 were conducted. The corresponding HOR electrochemical performance tests were also conducted. The results are as follows: Fig.10 and Fig.11 As shown. Fig.10 It can be seen that, to a certain extent, the current density decreases when the Pt loading increases, indicating that the increase in Pt loading causes the single atomic structure of Pt single atoms to be transformed into nanoclusters / particles, thereby reducing the number of active sites and affecting the electrochemical performance. At the same time, too little Pt metal loading makes the number of Pt single atoms too low and the metal active sites insufficient, so the ratio of Pt to Ir in Example 1 is the optimal ratio. Correspondingly, Co metal is the main metal that forms a carbon nanotube template together with Zn and folic acid, and its different loadings also have a significant effect on the electrochemical performance. Fig.11 It shows that, to a certain extent, the electrochemical performance of the catalyst increases with the increase of Co metal loading; and when the molar ratio of folic acid to Co is lower than 2:1, the electrochemical performance begins to decline; among them, the optimal electrochemical loading is when the molar ratio of folic acid to Co is 2:1.

[0107] Further, the carbon nanotube-supported PtIr diatomic Co alloy catalyst PtIr prepared in Example 1 was used. DA -Co NP The current-time (IT) stability test and CO desorption (CO stripping) test were carried out respectively. Specifically, a three-electrode system was used, 0.5 M H2SO4 was used as the electrolyte, and the IT and CO stripping tests were carried out on the Shanghai Chenhua CHI760e electrochemical workstation. The IT test was carried out at a constant voltage at a potential of 20 mV. In CO stripping, the working electrode was immersed in a CO-saturated electrolyte and adsorbed at a constant voltage at a potential of 0.1 V for 10 minutes, and then N2 was purged for 30 minutes to remove CO in the electrolyte. Subsequently, a cyclic voltammetry test was carried out under N2 conditions. The test voltage range was -0.05~1.05 V, and the scan rate was 50 mV / s. The data of the first two cycles were saved at the end of the test.

[0108] IT test results such as Fig.12 The results show that PtIr DA -Co NP After more than 20 h, the current density decreased by only 2.77%, which indicates that PtIr DA -Co NP It has excellent stability. The CO stripping test results are as follows Fig.13 The results show that compared with commercial Pt / C catalysts, PtIr DA -Co NP It has a lower CO desorption potential, which indicates that the energy barrier required for CO desorption is lower and it has good resistance to CO poisoning.

[0109] The above specific implementation method part specifically introduces the analytical method involved in the present invention. It should be noted that the above introduction is only to help those skilled in the art better understand the method and ideas of the present invention, rather than limiting the relevant content. Without departing from the principle of the present invention, those skilled in the art may also make appropriate adjustments or modifications to the present invention, and the above adjustments and modifications shall also fall within the scope of protection of the present invention.

Claims

1. A method for preparing a carbon nanotube-supported PtIr diatomic Co alloy catalyst, characterized in that: The steps include: (1) placing folic acid in a solvent and stirring; then sequentially adding a cobalt source, a platinum source, an iridium source and a zinc source and continuing stirring; then adding hydrazine monohydrate and stirring sufficiently to obtain a metal-folic acid mixed solution; the molar ratio of the folic acid to the cobalt element in the cobalt source is 1.5-2.5:1; the molar ratio of the folic acid to the platinum element in the platinum source is 15-25:1; the molar ratio of the folic acid to the iridium element in the iridium source is 10-40:1; the molar ratio of the folic acid to the zinc element in the zinc source is 1-15:1; the molar ratio of the platinum element in the platinum source to the iridium element in the iridium source is 0.7-1.5:1; (2) subjecting the metal-folic acid mixed solution to a hydrothermal reaction, and cooling to room temperature to obtain a metal-folic acid nanotube precursor; the temperature of the hydrothermal reaction is 100-200° C.; (3) washing the metal-folate nanotube precursor under high-speed centrifugation conditions; (4) freeze-drying the washed product, and then calcining it at high temperature under a protective gas atmosphere to obtain the product; the temperature of the high temperature calcination is 700-1200°C.

2. The preparation method according to claim 1, characterized in that The hydrothermal reaction time in step (2) is 60-180 min.

3. The preparation method according to claim 1, characterized in that: The solvent used for washing in step (3) is selected from one or more of water and ethanol, and the number of washing times is 1-10 times.

4. The preparation method according to claim 1, characterized in that The high temperature calcination in step (4) is specifically: heating to 700-1200° C. at a heating rate of 1-10° C. / min and calcining for 30-180 min.

5. Use of the carbon nanotube-supported PtIr diatomic Co alloy catalyst prepared by the preparation method according to any one of claims 1 to 4 in a fuel cell anode.

Citation Information

Patent Citations

  • Electrode catalyst for fuel cell and fuel cell

    CN101048902A

  • N-doped microporous carbon sphere ORR catalytic material and preparation method and application thereof

    CN110038612A